Pengaruh Kualitas Produk dan Iklan terhadap Minat Beli Konsumen Produk Bedak Tabita Skincare - Sri Winda Hardiyanti Damanik; Rakhmawati Purba (Ekonomis: Journal of Economics and Business, 2020)
This study aims to determine the quality of products and advertisements on consumer buying interest for Tabita powder skin care products. The results of data duplication using the SPSS 25 program for Windows generated multiple regression analysis with two independent variables and one dependent variable showing Y = 2,879 + 0,161X1 - 0,004X1 - Consumer Purchase Interest according to Product Demand and Advertising. The results of the analysis also obtained a coefficient of determination (R2) of 0.426 or 42.6%, which means that Consumer Purchase Interest can provide by the Product Quality and Advertising variables, while the percentage of 57.4% can be stated by other variables that do not apply in this study. Hypothesis testing on 1 statement that: the value of Product Quality if the value of tcount 3.001> ttable 2.002 and a significance level of 0.004 <0.05, it means that Product Quality affects Consumer Purchase Interest and Hypothesis 1 is accepted. Testing Hypothesis 2 states that: the value of advertising can be seen from the table 4.12 tcount -0.073 <ttable 2.002 and the significance level of the significance value is 0.942> 0.05, meaning that advertising has no effect on Consumer Purchase Interest and Hypothesis 2 is rejected. The test states that the value of Fcount is 15,590> Ftable 2.77 and a significance level of 0.000 <0.05 means that Product Quality and Advertising have a simultaneous effect on Consumer Purchase Interest and Hypothesis 3 is accepted.